Literature Review on Tennis-Based Physical Education Learning for Fitness - Hakim, Hikmad; Ishak, Muhammad; Bismar, Ahmad Rum (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This literature review examines the effects of tennis-based physical education (PE) on fitness development among students. A total of 15 recent studies conducted over the past decade were analyzed, encompassing elementary to university levels. The findings consistently demonstrate significant improvements in multiple fitness components due to tennis-based learning. Cardiovascular endurance increased by 15–20% following tennis drills lasting 8 to 12 weeks (Smith et al., 2015; Wijaya, 2020). Agility improved by 12% as a result of reaction-based tennis activities (Rahmawati, 2016). Balance and postural stability enhancements of 10–15% were observed in interventions reported by Chen & Lin (2017) and Tanaka & Ishikawa (2022). Furthermore, muscle strength in the upper and lower body increased by 10–18% due to tennis stroke and footwork training (Sulastri, 2021). Motor coordination improvements were noted in middle school students through longitudinal programs (Kwon et al., 2024). Despite these promising results, gaps exist, including limited longitudinal studies and underrepresentation of younger students and diverse geographical regions. The review highlights the importance of integrating tennis into PE curricula as a multidimensional tool to enhance physical fitness, cognitive skills, and motor development. Future research should focus on long-term impacts and include qualitative assessments to deepen understanding of student experiences. Overall, tennis-based PE offers a comprehensive approach to physical fitness development, promoting health and active lifestyles among youth.